Analysis of the Organizational Structure of the Sih Sah Somo Lumajang Community - Danang Wikan Carito; Riza Bahtiar Sulistyan; Moh. Hudi Setyobakti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The Sih Sah Somo Lumajang Art Organization Association is a performing organization focused on learning the arts of puppetry and karawitan. The purpose of this study was to find out the analysis of the organizational structure of the Sih Sah Somo Association of Lumajang Regency so that the positions and positions within the association organization are clear, the duties and responsibilities as well as control and supervision are going well. The research method uses descriptive qualitative research. The studio is domiciled in Sukodono District, Lumajang Regency. The number of members is 60 divided into 25 adults, 35 youths, 37 who are active until now and 2 coaches. After the job analysis was carried out, it was found that there were multiple positions, so an organizational structure proposal was made that was more in line with the specifications of each position so that it looked more focused in handling an organization. With the addition of managers and financial staff, they will focus more on dealing with problems in the organization by appointing or recruiting new members who are competent in these fields and have great responsibility in contributing to the community.